0
$\begingroup$

$1+2\sum_{n=1}^\infty \cos2n\pi x=\sum_{k=-\infty}^\infty \delta(x-k)$.

I couldn't have an idea to prove it, maybe we can discuss how to get it clearly.

$\endgroup$
  • $\begingroup$ that's called the Poisson summation formula $\endgroup$ – Abdelmalek Abdesselam Nov 14 at 22:37
0
$\begingroup$

I would integrate it and show that both sides are equal. The Dirac Delta is defined by its action under the integral, so it should be enough.

But I am physicists, so maybe it is more subtle.

$\endgroup$
  • $\begingroup$ Thanks. I know that to integrate it with the function in $C_C^\infty$ space, but I do not know the trick to prove the two integrals are equal. $\endgroup$ – Zhengqi Zhang Nov 14 at 9:34
0
$\begingroup$

We have that \begin{align*} 1+2\sum_{n=1}^\infty \cos 2n\pi x=\sum_{k=-\infty}^\infty \exp(2k\pi i x), \end{align*} and the right side is the Dirichlet kernel which means that \begin{align*} &\int_{-\infty}^\infty \sum_{k=-\infty}^\infty \exp(2k\pi i x) \phi(x)dx\\ &=\lim_{N\to\infty}\int_{-\infty}^\infty 2\pi D_N(2\pi x)\phi(x)dx\\ &=\lim_{N\to\infty}\left[\cdots+\int_{-\frac{3}{2}}^{-\frac{1}{2}}2\pi D_N(2\pi x)\phi(x)dx+\int_{-\frac{1}{2}}^{\frac{1}{2}}2\pi D_N(2\pi x)\phi(x)dx+\int_{\frac{1}{2}}^{\frac{3}{2}}2\pi D_N(2\pi x)\phi(x)dx+\cdots\right]\\ &=\lim_{N\to\infty}\left[\cdots+\int_{-3\pi}^{-\pi} D_N(t)\phi(\frac{t}{2\pi})dt+\int_{-\pi}^{\pi} D_N(t)\phi(\frac{t}{2\pi})dt+\int_{\pi}^{3\pi} D_N(t)\phi(\frac{t}{2\pi})dt+\cdots\right], \end{align*} and by the periodicity($2\pi$) of Dirichlet kernel and Fourier convergence theorem we have \begin{align*} &\lim_{N\to\infty}\left[\cdots+\int_{-3\pi}^{-\pi} D_N(t)\phi(\frac{t}{2\pi})dt+\int_{-\pi}^{\pi} D_N(t)\phi(\frac{t}{2\pi})dt+\int_{\pi}^{3\pi} D_N(t)\phi(\frac{t}{2\pi})dt+\cdots\right]\\ =&\lim_{N\to\infty}\left[\cdots+\int_{-\pi}^{\pi} D_N(\tau)\phi(\frac{\tau-2\pi}{2\pi})d\tau+\int_{-\pi}^{\pi} D_N(\tau)\phi(\frac{\tau}{2\pi})d\tau+\int_{-\pi}^{\pi} D_N(\tau)\phi(\frac{\tau+2\pi}{2\pi})d\tau+\cdots\right]\\ =& \sum\limits_{k=-\infty}^\infty \phi(k), \end{align*} Therefore in the sense of distribution we know that \begin{align*} 1+2\sum\limits_{n=-\infty}^\infty \cos 2n\pi x=\sum\limits_{k=-\infty}^\infty \delta(x-k) \end{align*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.